2014
DOI: 10.5398/medpet.2014.37.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Swamp Forages from South Kalimantan on Local Goat Performances

Abstract: Forages in swamp area consist of grass and legumes that have good productivity and nutrient quality. This research was aimed to evaluate the potency of swamp forage on digestibility and performance of goats. There were 24 local male goats aged 10-12 months with initial body weight of 13.10±1.55 kg, allocated into 6 treatments. Those were control (R0): 60% grass and 40% legumes; (R1): 60% swamp forages and 40% concentrate; (R2): 100% swamp forages; (R3): 100% swamp forage hay; (R4): 100% swamp forage silage; (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…Rumput ini mengandung serat kasar dan lignin tinggi yang dapat mengakibatkan rumput kumpai sukar untuk dicerna. Sebelum diberikan pada ternak, rumput kumpai perlu dilakukan pengolahan terlebih untuk meningkatkan nilai gizinya (Fariani dan Abrar, 2008;Fariani dan Evitayani, 2008;Rostini et al, 2014;). Upaya yang dilakukan untuk meningkatkan kualitas nutrisi rumput kumpai adalah dengan melakukan suplementasi dengan menggunakan legum rawa dan legum pohon seperti kemon air (water mimmosa), daun akasia, dan lamtoro.…”
Section: Pendahuluanunclassified
“…Rumput ini mengandung serat kasar dan lignin tinggi yang dapat mengakibatkan rumput kumpai sukar untuk dicerna. Sebelum diberikan pada ternak, rumput kumpai perlu dilakukan pengolahan terlebih untuk meningkatkan nilai gizinya (Fariani dan Abrar, 2008;Fariani dan Evitayani, 2008;Rostini et al, 2014;). Upaya yang dilakukan untuk meningkatkan kualitas nutrisi rumput kumpai adalah dengan melakukan suplementasi dengan menggunakan legum rawa dan legum pohon seperti kemon air (water mimmosa), daun akasia, dan lamtoro.…”
Section: Pendahuluanunclassified
“…Potensi produksi hijauan rawa yaitu Kumpai Batu (Ishaemum polystachyum J. Press) mencapai 6924,4 kg BK/ha/thn, Kumpai Minyak (Hymenagnechne amplexiacaulis Haess) sebesar 7228,2 kg BK/ha/thn, Pipisangan (Ludwigia hyssopifolia) sebesar 5961,2 kg BK/ thn dan Beberasan (Polygonum barbatum L) sebesar 6227,9 kg BK/ ha/thn ( Rostini et al, 2014). Pemanfaatan hijauan rawa sebagai pakan ternak ruminansia belum banyak dimanfaatkan, walaupun ketersediaanya melimpah namun memiliki antinutrisi dalam bentuk tanin yang berkisar antara 1,02-16,26% (Rostini et al, 2013) Tanin merupakan salah satu jenis antinutrisi yang banyak terdapat pada beberapa jenis tumbuhan tropis.…”
Section: Pendahuluanunclassified
“…Fodder with enough nutrients content for fulfilling cattle's needs will result on good productivity; the fodder quality is very important for meat contribution (Cahyani et al, 2012). The study result of Rostini et al (2014) showed that fodder made from plantation and agricultural waste has limitation factor if it was directly given to cattle and it was less palatable for the cattle. In this case, technology was needed in the waste processing so that it could be palatable for cattle.…”
Section: Introductionmentioning
confidence: 99%